Pengaruh Terapi Coloring Body Part Terhadap Kecemasan Pada Anak Usia Prasekolah (The Effect of Coloring Body Part Therapy Towards Pre-School Children Anxiety) - Apri Budianto; Gunawan Irianto; Eny Noerkayatmi (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2020)
AbstractData on maternal and child health surveys in 2010 shows that in Indonesia there are 33.2% of 1,425 children affected by hospitalization. The impact of hospitalization on children and families is anxiety. Anxiety is an individual response to something unpleasant and experienced by all living things. Anxiety for hospitalization is most felt in preschool children 3-6 years. Coloring body part (coloring body parts) is one type of therapy to play coloring body parts for children aged 4 to 7 years. Coloring this body part aims to increase pre-school children's knowledge about body functions and as pre-treatment hospitalization, namely introducing the body parts treated or performed surgery. This study aims to determine the effect of coloring body part therapy on anxiety in pre-school age children in Mitra Husada Hospital. This research was conducted in July 2017 at Mitra Husada Hospital. This research is a quantitative research with Quasy Experimental research type that is research which reveal causal relationship by involving group of subject of sign of control. Subjects studied were pre-school age children who underwent treatment in child care at Partner Husada Pringsewu Hospital with a large sample of 24 respondents. The sampling technique used is consecutive sampling. Statistical test by using paired sample t-test test is performed to analyze the difference of anxiety score before and after intervention. The data collection tool used is questionnaire. From the results of the study showed that there is influence of coloring body part therapy on anxiety of pre school children who are treated in RS.Mitra Husada with p value = 0,006. Keywords: anxiety; coloring body part therapy AbstrakData survei kesehatan ibu dan anak tahun 2010 menunjukkan bahwa di Indonesia ada 33,2% dari 1.425 anak mengalami dampak hospitalisasi. Dampak hospitalisasi pada anak dan keluarga salah satunya adalah kecemasan. Kecemasan merupakan respon individu terhadap sesuatu keadaan yang tidak menyenangkan dan dialami oleh semua makhluk hidup sehari-hari. Kecemasan akan hospitalisasi paling dirasakan pada anak usia prasekolah 3-6 tahun. Coloring body part (mewarnai bagian tubuh) merupakan salah satu jenis terapi bermain mewarnai bagian tubuh untuk anak usia 4 sampai 7 tahun. Mewarnai bagian tubuh ini bertujuan untuk menambah pengetahuan anak pra sekolah tentang fungsi tubuh dan sebagai pre- treatment hospitalisasi, yakni mengenalkan bagian tubuh yang diobati atau dilakukan pembedahan. Penelitian ini bertujuan untuk mengetahui pengaruh terapi coloring body part terhadap kecemasan pada anak usia pra ekolah di RS.Mitra Husada. Penelitian ini dilakukan pada bulan Juli 2017 di RS.Mitra Husada. Penelitian ini merupakan penelitian kuantitatif dengan jenis penelitian Quasy Eksperimen yaitu penelitian yang mengungkapkan hubungan sebab akibat dengan melibatkan kelompok subyek tanda ada kontrol. Subjek yang diteliti adalah anak usia pra sekolah yang menjalani perawatan di ruang perawatan anak di Rumah Sakit Mitra Husada Pringsewu dengan besar sampek 24 responden. Teknik pengambilan sampel yang digunakan adalah consecutive sampling. Uji statistik dengan menggunakan uji paired sample t-test yaitu uji yang dilakukan untuk menganalisis perbedaan skor kecemasan sebelum dan sesudah intervensi. Alat pengumpulan data yang digunakan adalah kuisioner. Dari hasil penelitian menunjukkan bahwa ada pengaruh terapi coloring body part terhadap kecemasan anak usia pra sekolah yang dirawat di RS.Mitra Husada dengan nilai p value = 0,006. Kata Kunci: kecemasan; terapi coloring body part